"Ethics, politics, and social research / edited by Gideon sjoberg" - "Sjoberg, Gideon .(ed.)" (London, 1969)
The book Ethics, Politics and Social Research is explain the drawing on a growing consensus about the importance of community representation and participation for ethical research, community engagement has become a central component of scientific research, policy-making, ethical review, and technology design.
Keywords: Ethics